Sistem Pendukung Keputusan Penentuan Karyawan Kontrak Menjadi Karyawan Tetap Menggunakan Perbandingan Metode SAW Dan MABAC - Sri Wahyuni (U-NET Jurnal Teknik Informatika, 2023)
Bumi Menara Internusa is a company engaged in the sale and production of canned food. PT. Bumi Menara Internusa has many employees consisting of permanent employees and non-permanent employees so it is necessary to determine the labor employees to become permanent employees who are assessed based on the performance of the labor employees and are eligible to become permanent employees. The process of determining permanent employees is very important to do for the welfare of employees while working, for example the appointment of employees. However, the system that runs at the company is still semi-computerized, especially in determining the determination of workers to become permanent employees, so that the determination of labor transfer decisions is very difficult to determine. The process of assessing labor transfers is done manually by assessing the performance of workers in terms of attendance, responsibility, skill, achievement and discipline so that the value obtained by Human Resources Development (HRD) is less accurate and inefficient because errors often occur in determining the value of workers. Thus, the process of making labor transfer reports takes a long time and the reports received are less accurate. Labor performance appraisal is the result of a person as a whole during a certain period in carrying out tasks, such as work standards, targets, or targets / criteria that have been determined in advance and have been mutually agreed upon.